Polymer-MXene composite films formed by MXene-facilitated electrochemical polymerization for flexible solid-state microsupercapacitors. (June 2019) - Qin, Leiqiang; Tao, Quanzheng; Liu, Xianjie; Fahlman, Mats; Halim, Joseph; Persson, Per O.Å.; Rosen, Johanna; Zhang, Fengling
Abstract: Materials with tailored properties are crucial for high performance electronics applications. Hybrid materials composed of inorganic and organic components can possess unique merits for broad application by synergy between the advantages the respective material type offers. Here we demonstrate a novel electrochemical polymerization (EP) enabled by a 2D transition metal carbide MXene for obtaining conjugated polymer-MXene composite films deposited on conducting substrates without using traditional electrolytes, indispensable compounds for commonly electrochemical polymerization. The universality of the process provides a novel approach for EP allowing fast facile process for obtaining different new polymer/MXene composites with controlled thickness and micro-pattern. Furthermore, high performance microsupercapacitors and asymmetric microsupercapacitors are realized based on the excellent composites benefiting from higher areal capacitance, better rate capabilities and lower contact resistance than conventional electropolymerized polymers. The AMSCs exhibit a maximum areal capacitance of 69.5 mF cm −2, an ultrahigh volumetric energy density (250.1 mWh cm −3 ) at 1.6 V, and excellent cycling stability up to 10000 cycles. The excellent electrochemical properties of the composite polymerized with MXene suggest a great potential of the method for various energy storage applications. Graphical abstract: Image 1 Highlights: Here we first realizing electrochemical polymerizing EDOT and Pyrrole using 2D MXenes to replace traditional electrolytes. Patterned composite films with microstructures can be deposited on any conductive substrates by in-situ polymerization. An all pseudocapacitive asymmetric microsupercapacitors were developed based on the PEDOT-MXene composite films and MnO2 . The AMSCs with an ultrahigh energy density and power density at a voltage window of 1.6 V.